BIOASSAY OF BOTANICAL OILS AGAINST ALTERNARIA SOLANI - Parveen, Tahira; Sharma, Kanika (International Journal of Current Pharmaceutical Research, 2018)
Objective: In vitroÂ antifungal activity of six essential oils of 1. Ocimum tenuiflorum (Purple leaves/Krishna Tulsi) 2. Cymbopogon citrates (Nimbu ghas), 3. Origanum majorina (Sweet majoram), 4. Ocimum citriodorum (Nimbu tulsi), 5. Ocimum bascillicum (Gulal tulsi), and 6. Ocimum sanctum (Green leaves/Shree tulsi) were investigated against economically important phytopathogenic fungi, Alternaria solani, isolated from infected chilly. Methods: The experiment was carried out by Whatman paper disc method using Whatman paper No.3 on Potato Dextrose Agar with three replicates. Five concentrations of each essential oils i.e., 20, 40, 60, 80 and 100% were assayed against the test fungus. The experiment was carried out at 27áµ’C and mycelial growth was measured after every third day, upto 15 d using statistical method. Results: It is an evident from this study that all the oils used in this study are inhibiting test fungi, oil of O. bascillicum and O. sanctum are completely (100%) inhibiting test fungi. Conclusion: It may be concluded from the above study that all the taken oils have a good potential to control plant pathogenic fungi and these could be considered for developing a new fungicide.